Imagination in Coleridge’s "Dejection: an Ode" - Fatima Alajily Saleh, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
This research paper aims to analyze the role of imagination in Samuel Taylor Coleridge's poem "Dejection: an ode". The poem that demonstrates the poet’s view of the relationship between human and Nature in an artistic way. Imagination is a prominent element in the creative poetic process of the romantic poets in general and Coleridge in particular. It also considers the position of dejection as a gate to the imaginative creativity. This research also emphasizes on the great significance of nature and imagination as they are the two essential themes in Coleridge’s works. It explains his frustration as he lacks the Muse, and how he resorts to imagination to enable him to have it once again. The study then shows that despite the inconsonant visions between the succession of the poet’s feeling and numbness expressed in his poem, he succeeded to achieve the strong fusion with nature again. It finally illustrates how the dejected Coleridge overcomes his dejection by the impact of imagination